A Reaction-Diffusion System with Nonlinear Nonlocal Boundary Conditions. (20th February 2014) - Gladkov, Alexander; Nikitin, Alexandr
Abstract : We consider initial boundary value problem for a reaction-diffusion system with nonlinear and nonlocal boundary conditions and nonnegative initial data. We prove local existence, uniqueness, and nonuniqueness of solutions.